2012
DOI: 10.1016/j.otsr.2012.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Trampoline fracture of the proximal tibial metaphysis in children may not progress into valgus: A report of seven cases and a brief review

Abstract: case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…In children, proximal tibial metaphyseal fractures are relatively uncommon injuries that occur between three and six years of age and are known as Cozen fractures (13,(18)(19)(20). They occur as complete or greenstick fractures of the proximal tibial metaphysis, with either no displacement or most commonly a lateral displacement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In children, proximal tibial metaphyseal fractures are relatively uncommon injuries that occur between three and six years of age and are known as Cozen fractures (13,(18)(19)(20). They occur as complete or greenstick fractures of the proximal tibial metaphysis, with either no displacement or most commonly a lateral displacement.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism produces the characteristic valgus metaphyseal fracture. The prototypic activity related to the development of proximal tibial metaphyseal fractures in children is trampoline jumping (13,19,22,23). Boyer and colleagues proposed that the injury is the result of a smaller child jumping on a trampoline with a larger individual, such that the descending child hits the recoiled mat from the larger person's jump at the exact time and with a hyperextended knee, re-sulting in a significant impaction force to the child's legs (22,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this situation is not always valid for trampoline-related fractures. [38] In a study performed by Hurson et al, [11] it was reported that more than half of the trampoline injuries led to fractures. Magnetic resonance imaging is useful for the diagnosis of fractures which are unable to be shown in the plain X-rays in painful situations due to trampoline injuries.…”
Section: Fracturesmentioning
confidence: 99%
“…I had the opportunity to publish a report of 7 cases with similar fracture few months following your report (2).…”
Section: Concerns: Trampoline Fracture Of the Proximal Tibiamentioning
confidence: 99%